2017
DOI: 10.1177/1179558117713016
|View full text |Cite
|
Sign up to set email alerts
|

Modern Contraceptive Choice Among Patients Seen at the “Cameroon National Planning Association for Family Welfare” Clinic Yaoundé

Abstract: BACKGROUNDTo understand the low modern contraceptive prevalence in Cameroon, we reviewed the methods chosen and determined their side effects among patients in an urban setting.METHODSWe conducted a cross-sectional study at the “Cameroon National Planning Association for Family Welfare (CAMNAFAW) Clinic” in Yaoundé. Data were processed by SPSS software version 20.0 for Windows, and all tests were considered statistically significant at P < .05.RESULTSOf the 1180 women sampled, the most chosen methods were as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
(7 reference statements)
3
8
0
Order By: Relevance
“…In Cameroon, LARCs are intended to be available through hospitals and selected clinics that provide family planning and reproductive health services. 34,35 However, a recent evaluation indicates that stock-outs prevail, with 70%-80% of facilities reporting stock-outs of each offered LARC method on the day of assessment. 36 The unmet need for contraception results in high numbers of unintended pregnancies.…”
mentioning
confidence: 99%
“…In Cameroon, LARCs are intended to be available through hospitals and selected clinics that provide family planning and reproductive health services. 34,35 However, a recent evaluation indicates that stock-outs prevail, with 70%-80% of facilities reporting stock-outs of each offered LARC method on the day of assessment. 36 The unmet need for contraception results in high numbers of unintended pregnancies.…”
mentioning
confidence: 99%
“…The most commonly used FP methods were implants and IUD in 29.4 and 28.4% of the participants respectively while the least used was condoms in 8.3% of the participants. The absence of male participants could be explained by the fact that FP is conceived by Cameroonians as concerning women coupled to the fact the FP clinic is located in the maternity widely attended by females [ 4 ]. Similar results with females predominant in FP have been gotten elsewhere in Cameroon [ 4 ] and Nigeria [ 3 ].…”
Section: Main Textmentioning
confidence: 99%
“…The absence of male participants could be explained by the fact that FP is conceived by Cameroonians as concerning women coupled to the fact the FP clinic is located in the maternity widely attended by females [ 4 ]. Similar results with females predominant in FP have been gotten elsewhere in Cameroon [ 4 ] and Nigeria [ 3 ]. A recent study by Njamen et al [ 13 ] in Douala Cameroon on acceptability of vasectomy demonstrated a low acceptability rate of vasectomy, a form of male contraception, by men influenced by sociocultural and religious barriers.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations